2021
DOI: 10.3390/molecules26020431
|View full text |Cite
|
Sign up to set email alerts
|

From Natural Products to New Synthetic Small Molecules: A Journey through the World of Xanthones

Abstract: This work reviews the contributions of the corresponding author (M.M.M.P.) and her research group to Medicinal Chemistry concerning the isolation from plant and marine sources of xanthone derivatives as well as their synthesis, biological/pharmacological activities, formulation and analytical applications. Although her group activity has been spread over several chemical families with relevance in Medicinal Chemistry, the main focus of the investigation and research has been in the xanthone family. Xanthone de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
56
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 67 publications
(58 citation statements)
references
References 174 publications
2
56
0
Order By: Relevance
“…Reserpine and carbonyl cyanide 3-chlorophenylhydrazone (CCCP) were used as positives control for S. aureus 272123 and SE03, respectively, at the sub-MIC concentration of 25 µM. [1][2][3][4][5][6][7][8][9][10][11] The value of the positive control in each different assay. SD: standard deviation.…”
Section: Efflux Pump Inhibition Assaymentioning
confidence: 99%
See 1 more Smart Citation
“…Reserpine and carbonyl cyanide 3-chlorophenylhydrazone (CCCP) were used as positives control for S. aureus 272123 and SE03, respectively, at the sub-MIC concentration of 25 µM. [1][2][3][4][5][6][7][8][9][10][11] The value of the positive control in each different assay. SD: standard deviation.…”
Section: Efflux Pump Inhibition Assaymentioning
confidence: 99%
“…Xanthones are heterocyclic polyphenolic compounds that can be found in microorganisms, fungi, lichens, and some in higher plants and marine sources, with several naturally and synthetically occurring derivatives revealing potent antimicrobial activities over the last few decades [10][11][12]. In recent works, our group described the synthesis of a series of novel nature-inspired chlorinated xanthones [13], and further transformations on the xanthone core in order to achieve a diverse library in terms of molecular function, containing carboxylic acid, ester, methyl, methoxy, phenol, bromo, and amine moieties [14].…”
Section: Introductionmentioning
confidence: 99%
“…Thioxanthones are compounds that possess a dibenzo-γ-pyrone, tricyclic scaffold, they are privileged structures [10] and they have previously been described as capable of modulating the human efflux pump P-gp [11]. Thioxanthones have also demonstrated their potential as antimicrobials and have proved to be effective in enhancing the activity of antibiotics in resistant bacterial strains [12].…”
Section: Introductionmentioning
confidence: 99%
“…Both X‐ray crystallography and nuclear magnetic resonance spectroscopy have revealed that SsnB, whose structural formula is C 15 H 8 O 4 , is a polyphenol (Figure 1A) containing two core components of xanthone and isocoumarin 10 . Xanthones have established antioxidant, anti‐inflammatory, immunomodulatory, anti‐tumour, antimicrobial, anticholinesterase and anticonvulsant functions 11‐14 . Similarly, Isocoumarins have anti‐tumour, anticoagulant, anti‐diabetes and antimicrobial bioactivities 15,16 .…”
Section: Introductionmentioning
confidence: 99%